2014
DOI: 10.1017/s1431927614001317
|View full text |Cite
|
Sign up to set email alerts
|

Whole Cell Cryo-Electron Tomography Suggests Mitochondria Divide by Budding

Abstract: Eukaryotes rely on mitochondrial division to guarantee that each new generation of cells acquires an adequate number of mitochondria. Mitochondrial division has long been thought to occur by binary fission and, more recently, evidence has supported the idea that binary fission is mediated by dynamin-related protein (Drp1) and the endoplasmic reticulum. However, studies to date have depended on fluorescence microscopy and conventional electron microscopy. Here, we utilize whole cell cryo-electron tomography to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
3
11
0
Order By: Relevance
“…Visual inspection of the mitochondria within the individual micrographs from patient and control cells revealed both spherical and tubular/elongated mitochondria, with closely apposed MIM and MOM, and an electron-dense matrix containing cristae and calcium/phosphorus ion granules ( Wolf et al., 2017 ) ( Figure S2 ). The appearance of these mitochondria was comparable to previous reports of in situ human mitochondria ( Hu, 2014 ) and consistent across both our patient and control samples. In addition, we found that the signal-to-noise ratio is considerably lower for in situ datasets compared with prior work using purified mitochondria ( Nicastro et al., 2000 ), as reflected in such parameters as mitochondrial matrix texture.…”
Section: Resultssupporting
confidence: 91%
“…Visual inspection of the mitochondria within the individual micrographs from patient and control cells revealed both spherical and tubular/elongated mitochondria, with closely apposed MIM and MOM, and an electron-dense matrix containing cristae and calcium/phosphorus ion granules ( Wolf et al., 2017 ) ( Figure S2 ). The appearance of these mitochondria was comparable to previous reports of in situ human mitochondria ( Hu, 2014 ) and consistent across both our patient and control samples. In addition, we found that the signal-to-noise ratio is considerably lower for in situ datasets compared with prior work using purified mitochondria ( Nicastro et al., 2000 ), as reflected in such parameters as mitochondrial matrix texture.…”
Section: Resultssupporting
confidence: 91%
“…[1][2][3]34 Recent observations based on cell cryoelectron tomography indicate that budding is the mitochondrial division mechanism. 59 Budding is also known in bacterial endospores, 60,61 and membraneenveloped viruses, 62-65 such as Poxviridae. Hence, the process of mitochondrial division also hints at possible origins of mitochondria and viruses from bacterial endospores.…”
Section: Cellular Origin Of Virusesmentioning
confidence: 99%
“…3e, SI). The mitochondrial envelope is composed of two membranes, which are constrained to be in close proximity at the constriction site [32]. Thus, as a first approximation, we considered both membranes as a composite system with a rigidity of 40 kBT, double the value of single lipid bilayers from in vitro measurements [33].…”
Section: Fission Events Are Characterized By Higher Bending Energymentioning
confidence: 99%